Multi-center study to analyse outcome of integrated treatment approach in COVID-19 patients - Purushothaman, Suraj; Dhotre, Prasant Kumar; Vanarase, Kamlesh Prakash; Jadhao, Gajanan Kisan; Maurya, Abhay Gyanchand; Gupta, Sanjay Mohanlal; Gawali, Vijaykumar (International Journal Of Community Medicine And Public Health, 2023)
Background: This study presents the outcome of integrated treatment approach based on government mandated standard allopathic treatment along with alternatives in COVID-19 patients. The aim of our study was to investigate the outcome of treatment strategy, co-morbid status, recovery and mortality rate of COVID-19 patients at Bhaktivedanta Hospital and Research Institute. Methods: Post ethics committee approval for multiple centers, data for 1049 COVID-19 patients (RTPCR confirmed cases) of all age groups and genders which were admitted in a dedicated covid hospital from March 2020 to November 2020 was analysed retrospectively. Results: This study highlights the management of COVID-19 patients with an integrated approach. In our cohort with 36.7%, 44.70 %, 18.58% of mild, moderate and severe cases respectively, mortality rate was only 3.43% of total positive patients admitted at our hospital. Conclusions: We emphasize that even in healthcare facilities with limited resource and poor infrastructure and lack of ICU facilities, clinical observation-based management can help to reduce mortality considerably. Unique features of our study include use of progesterone as an immune modulator, use of dual antiviral agents and use of age-related lower limit of oxygen saturation.